(untitled) (Studia Prawnicze / The Legal Studies, 2001)
Ustawodawca wprowadził zamkniętą listę form prawnoorganizacyjnych dostępnych dla banku. Art. 12 pr. bank. należy rozumieć w ten sposób, iż ograniczony wybór formy prawnej dla banku w momencie jego tworzenia dotyczy również okresu działalności banku. Tak więc zarówno utworzenie, jak i prowadzenie przedsiębiorstwa bankowego jest możliwe tylko w wyżej wymienionych formach prawnych. Roczny termin, o którym mowa w art. 38 pr. bank., biegnie od momentu wydania zezwolenia na utworzenie banku, zatem wniosek o wydanie zezwolenia na podjęcie działalności operacyjnej banku-spółki akcyjnej winien być złożony przed upływem tego terminu, co nie jest jednak wskazane w przepisach. The legislator has introduced a closed list of legal and organisational forms which a bank may assume. Article 12 of the Banking Act should be construed to mean that the limited choice of legal form for a bank at the time of its establishment also applies during the bank’s period of operation. Thus, both the establishment and operation of a banking company is only possible in the legal forms mentioned above. The one-year time limit referred to in Article 38 of the Banking Act runs from the moment the authorisation for the establishment of the bank is issued, so the application for authorisation to start the operational activities of a joint-stock bank should be submitted before the expiry of this time limit, which, however, is not indicated in the legislation.